ANALISIS BIBLIOMETRIK: MANAJEMEN RANTAI PASOKAN HIJAU (2023-2014): - Wahyuni, Hilda; Haryati, Teti; Yudha Heryawan Asnawi (Airlangga Journal of Innovation Management, 2024)
This research discusses the publication trend on the topic of green supply chain management with "Green Supply Chain Management" as the keyword. Search using the title and abstract categories listed in Dimension from 2014 to 2023 analyzed in a bibliometric study. This bibliometric study can guide academics and practitioners to take relevant steps in managing environmentally friendly supply chains. Therefore, this research could contribute to understanding developments and challenges in the green supply chain field. The results of this study are expected to provide insights for decision-makers and practitioners in managing supply chain sustainably. There are 4,017 articles. This number is very impressive and almost every year there is a significant development in this research topic. The analysis of this study is focused on the number of publications, authors, and journals. This study aims to observe the development map of Green Supply Chain Management research in the world. Results show that the number of publications on Green Supply Chain Management has increased quite steadily and was the most published in 2023 with a total of 803 journals. As for the lowest number of publications, there was in 2014 with the number of publications as many as 179. Thus, it can be concluded that the topic of this theme has developed from year to year, and this concept has great potential to develop further in the future.